Sedimentology of the Phra That and Pha Daeng Formations: A preliminary evaluation of geological CO2 storage potential in the Lampang Basin, Thailand - Moonpa Kritsada; Mankhemthong Niti; Banlue Hathairat; Kanthata Sathit; Chaibamrung Phongsakorn; Chueabunyuen Chiang (Open Geosciences)
The increasing levels of CO2 emissions have become a major concern for scientists and policymakers worldwide. As a result, they have been exploring various potential solutions to reduce CO2 levels, and one such solution is carbon capture and storage. Field observations, sedimentological analyses, diagenesis, and petrography were performed in a preliminary evaluation to assess the reservoir potential for geological CO2 storage in the Phra That and Pha Daeng Formations, Lampang Group. The succession can be divided into ten lithofacies types and grouped into three distinct depositional units, corresponding to a fluvial environment. The outcrop and subsurface core samples underwent distinct diagenetic processes that markedly influenced their reservoir properties. Primary porosity in outcrop samples has been reduced by iron oxide cements, followed by calcite cements and quartz overgrowth cements. The core samples reveal a considerable compaction, iron oxide, quartz overgrowth cementation, authigenic clay, and calcite, which ultimately reduced the porosity of the potential reservoir. Thus, the Phra That Formation is not suitable as a CO2 storage reservoir.